Single soliton microcomb combined with optical phased array for parallel FMCW LiDAR - Jingye Chen; Wenlei Li; Zhe Kang; Zongxing Lin; Shi Zhao; Daixin Lian; Jijun He; Dongmei Huang; Daoxin Dai; Yaocheng Shi (Nature Communications)
Abstract The frequency-modulated continuous-wave (FMCW) technology combined with optical phased array (OPA) is promising for the all-solid-state light detection and ranging (LiDAR). We propose and experimentally demonstrate a silicon integrated OPA combined with an optical frequency microcomb for parallel LiDAR system. For realizing the parallel wavelengths emission consistent with Rayleigh criterion, the wide waveguide beyond single mode region combined with the bound state in the continuum (BIC) effect is harnessed to obtain an ultra-long optical grating antenna array. The single soliton comb, generating about multiple distinct wavelength channels and combined with the high performance integrated OPA, is also demonstrated for coherent three-dimensional (3D) imaging by utilizing FMCW method. The modulation bandwidth of parallel modulation of the microcomb is beyond the modulation region of single soliton microcomb. The result paves the way for developing all-solid-state and ultrahigh-frame-rate coherent LiDAR systems.